Computational fluid analysis of blood flow characteristics in abdominal aortic aneurysms treated with suprarenal endovascular grafts - Sun, Zhonghua; Chaichana, Thanapong; Sangworasil, Manas; Tungjitkusolmun, Supan (My University, 2009)
The purpose of this study is to investigate the hemodynamic effects of suprarenal stent grafts on the renal arteries in the treatment of patients with abdominal aortic aneurysm. Suprarenal stent grafts have been increasingly used for treatment of aortic aneurysms with suboptimal aneurysm necks. However, the long-term safety of this procedure is yet to be determined. 2 sample patients undergoing suprarenal stent grafting were included in the study. Four variable configurations of stent wires crossing the renal artery ostium were simulated in aorta models based on CT generated data, at different cardiac cycles. The stent wires thickness was set 0.5 mm which is similar to the actual diameter of a stent wire. Computational fluid dynamic analysis showed slightly decrease of flow velocity to the renal arteries with multiple wires crossing, and no changes of flow velocity to the renal arteries with single wire crossing. Our preliminary results demonstrated the safety of suprarenal stent grafting. Further studies are required to investigate the effect of different wire thickness on subsequent hemodynamic changes to the renal arteries.
Keywords: Aortic aneurysm; Blood flow; Stent graft; Suprarenal stent